Heat Stress in Livestock: Impacts and Ameliorative Strategies—a Review - Sailo, Lalrengpuii; Das, Ramendra (International Journal of Bio-resource and Stress Management, 2023)
Heat stress is one of the most important climatic conditions which adversely affects agricultural and livestock production worldwide. High ambient temperature with direct and indirect solar radiation, wind speed and relative humidity impose thermal stress in animals. The foremost reaction of animals under thermal weather is increased respiration and pulse rate, and rectal temperature. It directly affects feed intake thereby, reduces growth rate, milk yield, reproductive performance and even death in extreme cases. Heat stress suppresses the immune system thereby enhances susceptibility of an animal to various diseases. It is very important to control the impacts of thermal stress for sustainable dairy farming. Advances in environmental modifications and nutritional management in part alleviate the impact of thermal stress on animal performance during the hotter seasons. However, long-term strategies have to be evolved for adaptation to climate change. Differences in thermal tolerance between livestock species provide clues to select thermotolerant animals using genetic tools. There are heat shock gene related to thermotolerance that was identified and being used as marker in marker-assisted selection and genome-wide selection to develop thermotolerant bull that is used in breeding program. The present review collates and synthesizes information pertaining to thermal shock and possible ameliorative strategies to combat the impacts in livestock.